Post-transactional customer service in a company’s competitive approach – results of the study - Walasek, Robert (Potransakcyjna obsługa klienta w podejściu konkurencyjnym przedsiębiorstwa – wyniki badań, 2019)
The main objective of this paper is to attempt to characterize the post-transactional impact of customer service on building the competitiveness of a company. The article discusses the importance of post-transactional customer service and indicates its key impact on building long-term relationships by maximizing value for the customer. The benefits that the company achieves by using selected techniques and strategies that ensure the clear identification of clients’ needs and preferences are shown. The paper also presents a discussion and results of empirical research regarding the impact of post-transaction customer service on building a company’s competitiveness by creating relationships with customers. The results of the research showed that the implementation of post-transactional activities at every level of an organization’s operation contributes to effective customer service and brings tangible benefits by increasing the efficiency of the supply chain, as well as affecting the creation of added value for the customer
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 200-211
Keywords: post-transactional service; supply chain; competitiveness; customer; relationship; obsługa potransakcyjna; łańcuch dostaw; konkurencyjność; klient; relacje